Organizational Cosmopolitanism and Innovativeness - Robertson, Thomas S.; Wind, Yoram (Academy of Management Journal, 1983)
The article discusses a research on organizational cosmopolitanism and innovativeness. Individual cosmopolitanism scores were correlated against the number of innovations adopted by the organizatio...